Pengaruh Profitabilitas, Solvabilitas, Likuiditas, dan Kompleksitas Operasi terhadap Audit Delay: Studi Empiris pada Perusahaan Property and Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Hardiyanti, Adelis Kus; Setiawan, Mia Angelina (Jurnal Nuansa Karya Akuntansi, 2023)
The primary key of this study is to examine the influence of profitability, solvency, liquidity and operational complexity. This research uses audited financial report data From real estate and property firms publicly traded on the Indonesia Stock Exchange (IDX)) from 2018 to 2022. Hypothesis testing is carried out through regression analysis multiple linear. The research results show that profitability and operational complexity have a significant positive impact on the delay in auditing. Solvency and liquidity have a significant negative effect on audit delay.